The effectiveness of mental health mobile application on postpartum depression in postpartum mothers: A systematic review - Rahmawati; Astika; Viana Bari Umaroh; Dulce Maria Guterres; Cesa Septiana Pratiwi; Rizki Tsalatshita Khair Mahardya (Universitas Aisyiyah Yogyakarta, 2025)
Significant mental health issues in postpartum mothers have an impact on both mothers and child development. Limited access to services and social stigma hinder treatment. Mental health-based mobile applications have emerged as a potential alternative intervention. The objective of the research was to analyze the effectiveness of mobile applications in reducing postpartum depression symptoms and the factors contributing to their success. A systematic review following the PRISMA 2020 guidelines was conducted, searching PubMed, Wiley, ProQuest, and Google Scholar for articles published between 2020 and 2025. Ten quantitative and qualitative articles were analyzed. Apps using cognitive behavioral therapy (CBT), mindfulness, and telecounseling approaches were effective in reducing postpartum depression symptoms. Success was influenced by user-friendly design, social support, cultural sensitivity, and integration with healthcare services. Barriers included low digital literacy, stigma, and privacy concerns. Mobile apps have the potential to be an effective and affordable solution. In Indonesia, development should prioritize scientific evidence, ease of use, and integration with primary healthcare services.